2010
DOI: 10.1186/1471-2407-10-618
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic canine mammary carcinomas can be identified by a gene expression profile that partly overlaps with human breast cancer profiles

Abstract: BackgroundSimilar to human breast cancer mammary tumors of the female dog are commonly associated with a fatal outcome due to the development of distant metastases. However, the molecular defects leading to metastasis are largely unknown and the value of canine mammary carcinoma as a model for human breast cancer is unclear. In this study, we analyzed the gene expression signatures associated with mammary tumor metastasis and asked for parallels with the human equivalent.MethodsMessenger RNA expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 50 publications
(53 reference statements)
6
113
1
3
Order By: Relevance
“…The percentage of GrB + cells was calculated by counting all lymphocytic cells per complete longitudinal section of cerebrum and cerebellum, and the number of all GrB + lymphocytic cells per complete longitudinal section of cerebrum and cerebellum. The presence of intravascular leukocytes, endothelial activation, and vessel wall hyalinization was evaluated in sagittal H&E-stained sections of the cerebrum and cerebellum as described previously (39). The presence of intravascular leukocytes was evaluated positive (score 1) if the majority of intracerebral and intracerebellar vessels contained more than one nucleated cells or were otherwise scored as 0.…”
Section: Brain Histologymentioning
confidence: 99%
“…The percentage of GrB + cells was calculated by counting all lymphocytic cells per complete longitudinal section of cerebrum and cerebellum, and the number of all GrB + lymphocytic cells per complete longitudinal section of cerebrum and cerebellum. The presence of intravascular leukocytes, endothelial activation, and vessel wall hyalinization was evaluated in sagittal H&E-stained sections of the cerebrum and cerebellum as described previously (39). The presence of intravascular leukocytes was evaluated positive (score 1) if the majority of intracerebral and intracerebellar vessels contained more than one nucleated cells or were otherwise scored as 0.…”
Section: Brain Histologymentioning
confidence: 99%
“…On the contrary in the present study Bax expression was higher only in tumours in T5 stage (P<0.05). Although there is no sufficient data about the pathogenetic meaning of overexpression of Bax in metastatic tumours, it was reported that proapoptotic and anti-apoptotic gene transcription increases significantly in metastatic tumours [33] . This finding can be explanatory for both Bax and Bcl-2 results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…A similar decreased receptor expression with increasing malignancy has been described in several canine tumors before, including the serotonin receptor on canine MCT and several growth factor receptors on metastatic canine mammary carcinomas. 8,[20][21][22] This down-regulation of mostly proliferative but also inhibitory receptors therefore seems to be a common mechanism in canine tumors and reflects the increasing independency of malignant tumors from external proliferation stimuli when compared with benign tumor variants or nonneoplastic cells.…”
Section: Discussionmentioning
confidence: 99%